The difference of PGE2 and COX-2 expressions in various histological grading of endometrial endometrioid carcinoma - Yusfita Evi Rosdiana; Willy Sandhika (Majalah Obstetri dan Ginekologi, 2017)
Objectives: to analyze the expression of PGE2 and COX-2 in various histological grade of endometrial endometrioid carcinoma.Materials and Methods: Analytical observational study was performed on parafin block archives of endometrial endometrioid carcinoma with histological grade 1,2 and 3 in Anatomic Pathology laboratory Dr. Soetomo hospital. PGE2 and COX-2 expression were examined by immunohistochemical staining using PGE2 and COX-2 antibodies. The results were analyzed statistically.Results: There were increase of PGE2 expressions of in endometrioid carcinoma grade 2 compare to  grade 1 and grade 3 compare to grade 2. The COX-2 expression was increase in histologic grade 3 compare to grade 1.Conclusion: The expression of PGE2 and COX-2 in endometrial endometrioid carcinoma were increased in higher histologic grade compare to lower histologic grade.